METROLOGICAL MAINTENANCE OF MEASUREMENT OF THERMAL CONDUCTIVITY PARAMETERS - N. A. Zhagora; P. S. Serenkov; O. V. Fufaeva (Приборы и методы измерений, 2015)
A two-stage method of intralaboratory research of characteristics of accuracy of the method of measurement  of  thermal  conductivity  was  developed  and  implemented.  The  criterion  determining  the necessity of performing the second stage of research was formulated. The technique allows to identify sources influenced on the result of measurement of thermal conductivity, and also to control characteristics of the method (precision). Recommendations for research of the National reference unit of thermal conductivity were developed.